FUZZY ISOMORPHISM THEOREMS OF SOFT GROUPS - Pan, Wenjun; Wang, Qiumei; Zhan, Jianming (Italian Journal of Pure and Applied Mathematics, 2015)
In this paper, we introduce the concept of fuzzy normal subgroups of soft groups. The first, second and third fuzzy isomorphism theorems of soft groups are established, respectively. In particular, some classes of quotient groups are characterized by their fuzzy normal subgroups.